2014
DOI: 10.1128/mcb.01216-13
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 Transcriptional Activity by SMRT: a Histone Deacetylase 3-Independent Function of a Transcriptional Corepressor

Abstract: The silencing mediator of retinoic acid and thyroid hormone receptors (SMRT) is an established histone deacetylase 3 (HDAC3)-dependent transcriptional corepressor. Microarray analyses of MCF-7 cells transfected with control or SMRT small interfering RNA revealed SMRT regulation of genes involved in DNA damage responses, and the levels of the DNA damage marker ␥H2AX as well as poly(ADP-ribose) polymerase cleavage were elevated in SMRT-depleted cells treated with doxorubicin. A number of these genes are establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 83 publications
(131 reference statements)
3
15
0
Order By: Relevance
“…Here, our data provide the first evidence that the inhibition of HDAC3 by lentivirus‐mediated shRNA in the hippocampus attenuates spatial memory deficits and decreases amyloid plaque load and Aβ levels in 9‐month‐old APP/PS1 mice. We speculate that at least the three following reasons contribute to the inconsistence of these studies: (i) lentivirus‐mediated inhibition of HDAC3 is used in this study, which inhibits not only deacetylase activity but also the expression of HDAC3 (considering that HDAC3 also has several deacetylase‐independent functions (Sun et al ., ; Adikesavan et al ., ), inhibition of the expression using a genetic knockout or knockdown approach might be more reasonable); (ii) RGFP966 is IP injected for 12 days at a dose of 30 mg kg −1 as previously described, but the time‐dependent and dose‐dependent effects of RGFP966 on the memory function of APP/PS1 mice are not shown; and (iii) although contextual fear conditioning and MWM tests are generally considered hippocampus‐dependent tasks, there are different brain regions involved, which might lead to inconsistent results (Puzzo et al ., ). Interestingly, inhibition of HDAC3 activity by RGFP966 augments LTP and re‐establishes synaptic tagging and capture in aged hippocampal CA1 neurons (Sharma et al ., ), which indicated that HDAC3 might contribute to both normal aging and AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Here, our data provide the first evidence that the inhibition of HDAC3 by lentivirus‐mediated shRNA in the hippocampus attenuates spatial memory deficits and decreases amyloid plaque load and Aβ levels in 9‐month‐old APP/PS1 mice. We speculate that at least the three following reasons contribute to the inconsistence of these studies: (i) lentivirus‐mediated inhibition of HDAC3 is used in this study, which inhibits not only deacetylase activity but also the expression of HDAC3 (considering that HDAC3 also has several deacetylase‐independent functions (Sun et al ., ; Adikesavan et al ., ), inhibition of the expression using a genetic knockout or knockdown approach might be more reasonable); (ii) RGFP966 is IP injected for 12 days at a dose of 30 mg kg −1 as previously described, but the time‐dependent and dose‐dependent effects of RGFP966 on the memory function of APP/PS1 mice are not shown; and (iii) although contextual fear conditioning and MWM tests are generally considered hippocampus‐dependent tasks, there are different brain regions involved, which might lead to inconsistent results (Puzzo et al ., ). Interestingly, inhibition of HDAC3 activity by RGFP966 augments LTP and re‐establishes synaptic tagging and capture in aged hippocampal CA1 neurons (Sharma et al ., ), which indicated that HDAC3 might contribute to both normal aging and AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the SMRT knockin mutation used in these studies only abrogated its interaction with nuclear receptors but retained its ability to bind Hdac3. Recent studies have also implicated that SMRT has Hdac3-independent functions in some contexts (Adikesavan et al, 2014), and that SMRT and NCoR have non-redundant in vivo functions (Mottis et al, 2013; Sun et al, 2013), suggesting that despite the co-existence of Hdac3 and SMRT in the same complex, these two proteins are not completely interchangeable in their molecular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Both TBL1 and TBLR1 possess F-box like motifs which mediate interaction with ubiquitin ligases. Like GPS2, both TBL1 and TBLR1 are also involved in transcriptional activation (Adikesavan et al, 2014; Li and Wang, 2008; Perissi et al, 2004). AR downregulates the expression of all three cofactors of the corepressor complex.AR expression leads to reduced HDAC3-corepressor complex formation in two ways: (i) AR competes with HDAC3 for its interaction with the corepressor, leading to free HDAC3 for degradation; (ii) AR leads to downregulation of all accessory factors required for corepressor complex formation including Gps2 , Tbl1 , and Tbl1xr .…”
Section: Discussionmentioning
confidence: 99%